Attenuation of offset analgesia is associated with suppression of descending pain modulatory and reward systems in patients with chronic pain. Issue 1 (March 2018) - Zhang, Shuo; Li, Tianjiao; Kobinata, Hiroyuki; Ikeda, Eri; Ota, Takashi; Kurata, Jiro
Background: Offset analgesia is a disproportionate decrease of pain perception following a slight decrease of noxious thermal stimulus and attenuated in patients with neuropathic pain. We examined offset analgesia in patients with heterogeneous chronic pain disorders and used functional magnetic resonance imaging to explore modification of cerebral analgesic responses in comparison with healthy controls. Results: We recruited seventeen patients with chronic pain and seventeen age-, sex-matched healthy controls. We gave a noxious thermal stimulation paradigm including offset analgesia and control stimuli on the left volar forearm, while we obtained a real-time continuous pain rating and a whole-brain functional magnetic resonance imaging. Baseline, first plateau (5 s), increment (5 s), and second plateau (20 s) temperatures of offset analgesia stimulus were set at 32°C, 46°C, 47°C, and 46°C, respectively. Control stimulus included 30-s 46°C stimulus or only the first 10 s of offset analgesia stimulus. We evaluated magnitude of offset analgesia, analyzed cerebral activation by thermal stimulation, and further compared offset analgesia-related activation between the groups. Magnitude of offset analgesia was larger in controls than in patients (median: 28.9% (interquartile range: 11.0–56.0%) vs. 19.0% (4.2–48.7%), p  = 0.047). During the second plateau, controls showed a larger blood oxygenation level-dependent activation than patients at the putamen, anterior cingulate, dorsolateral prefrontal cortices, nucleus accumbens, brainstem, and medial prefrontal cortex ( p  < 0.05), which are known to mediate either of descending pain modulation or reward responses. Offset analgesia-related activity at the anterior cingulate cortex was negatively correlated with neuropathic component of pain in patients with chronic pain ( p  = 0.004). Conclusions: Attenuation of offset analgesia was associated with suppressed activation of the descending pain modulatory and reward systems in patients with chronic pain, at least in the studied cohort. The present findings might implicate both behavioral and cerebral plastic alterations contributing to chronification of pain. Clinical trial registry: The Japanese clinical trials registry (UMIN-CTR, No. UMIN000011253;http://www.umin.ac.jp/ctr /)